2021
DOI: 10.3389/fmicb.2021.749760
|View full text |Cite
|
Sign up to set email alerts
|

Alone Yet Not Alone: Frankia Lives Under the Same Roof With Other Bacteria in Actinorhizal Nodules

Abstract: Actinorhizal plants host mutualistic symbionts of the nitrogen-fixing actinobacterial genus Frankia within nodule structures formed on their roots. Several plant-growth-promoting bacteria have also been isolated from actinorhizal root nodules, but little is known about them. We were interested investigating the in planta microbial community composition of actinorhizal root nodules using culture-independent techniques. To address this knowledge gap, 16S rRNA gene amplicon and shotgun metagenomic sequencing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
(117 reference statements)
0
12
1
Order By: Relevance
“…Root microbiome of C. myrtifolia contained Actinobacteria, Proteobacteria, Firmicutes, Cyanobacteria, Bacteroidetes , and others, which is very similar to composition of Alnus glutinosa root microbiome ( Thiem et al, 2018 ), Casuarina glauca ( Ghodhbane-Gtari et al, 2021 ), several Legume roots ( Miranda-Sánchez et al, 2016 ; Xiao et al, 2017 ; Zgadzaj et al, 2016 ), and rice ( Edwards et al, 2015 ; Roman-Reyna et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Root microbiome of C. myrtifolia contained Actinobacteria, Proteobacteria, Firmicutes, Cyanobacteria, Bacteroidetes , and others, which is very similar to composition of Alnus glutinosa root microbiome ( Thiem et al, 2018 ), Casuarina glauca ( Ghodhbane-Gtari et al, 2021 ), several Legume roots ( Miranda-Sánchez et al, 2016 ; Xiao et al, 2017 ; Zgadzaj et al, 2016 ), and rice ( Edwards et al, 2015 ; Roman-Reyna et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
“…It is commonly accepted that actinorhizal nodules are a special niche for symbiotic nitrogen fixation, which is primarily colonized by Frankia. However, as it has been shown by the culturedependent and -independent methods, several non-Frankia coexist with Frankia (Ghodhbane- Gtari et al, 2010bGtari et al, , 2021; Ghodhbane- Gtari and Tisa, 2014). At phylum level, the C. myrtifolia nodule microbiome differs from root only in term of relative abundance of each phylum and being composed of Bacteroidetes, Proteobacteria, and Actinobacteria.…”
Section: Rhizocompartment Microbiomesmentioning
confidence: 94%
“…Recently other studies have confirmed this nodule surface emplacement of Casuarina incompatible Frankia strains. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to assert the influence this may have had on results as little is known regarding the determinants of microbial diversity in nodules. In a study of Casuarina glauca nodules sourced in the natural environment, Ghodhbane-Gtari et al (2021) noted that water stress is one element that may have an impact on microbial diversity, specifically Frankia sp. sequence proportion in relation to total OTUs.…”
Section: Alder Nodule Bacterial Community Diversitymentioning
confidence: 99%